The role of humble leadership in empowering human resources: A field study exploring the opinions of a sample of educational staff in the Al-Ameed Educational Group. - Ahmed Al-eqabi, Abbas; Salem Al-Janabi, Yazan (Iraqi Journal for Administrative Sciences, 2023)
This aims to demonstrate the role of modest leadership in empowering human resources, and the research started with a main problem that included several questions revolving around the nature of the relationship between its variables in the field, the most important of which was (Does modest leadership influence the empowerment of human resources in the organization in question?). Using the descriptive analytical approach, the data were collected through a questionnaire, and the study population included a sample of educational staff in the Dean’s educational group affiliated with the al-Abbas’s (p) Holy Shrine. The study sample reached (196) employees, and for the purpose of data analysis and statistical processing, the research relied on a set of statistical methods available in Ready-made programs (SPSS V. 23; Amos V.23; Microsoft Excel 2010). The research reached a set of conclusions, the most important of which is the existence of two significant correlation and effect between modest leadership in its sub-dimensions and empowerment of human resources, and finally the research concluded with a set of recommendations, the most important of which are the necessity of Investing the positive impact of humble leadership in empowering human resources through the organization in question employing humble leadership in all areas its divisions and activities.